2016
DOI: 10.18632/oncotarget.11731
|View full text |Cite
|
Sign up to set email alerts
|

Vitexin suppresses autophagy to induce apoptosis in hepatocellular carcinoma via activation of the JNK signaling pathway

Abstract: Vitexin, a flavonoids compound, is known to exhibit broad anti-oxidative, anti-inflammatory, analgesic, and antitumor activity in many cancer xenograft models and cell lines. The purpose of this study was to investigate the antitumor effects and underlying mechanisms of vitexin on hepatocellular carcinoma. In this study, we found that vitexin suppressed the viability of HCC cell lines (SK-Hep1 and Hepa1-6 cells) significantly. Vitexin showed cytotoxic effects against HCC cell lines in vitro by inducing apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…35 He's research elucidated that vitexin suppressed autophagy in hepatocellular carcinoma. 15 Whether vitexin suppressed autophagy in cardiomyocytes during MI/R was still remained unclear. In this present study, we found that vitexin treatment markedly decreased Beclin1, LC3I/II protein level and the number of GFP-LC3 dots while increased p62 protein level compared to MI/R model group, suggesting that vitexin may improve myocardial damage by inhibiting autophagy of cardiomyocytes in MI/R injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 He's research elucidated that vitexin suppressed autophagy in hepatocellular carcinoma. 15 Whether vitexin suppressed autophagy in cardiomyocytes during MI/R was still remained unclear. In this present study, we found that vitexin treatment markedly decreased Beclin1, LC3I/II protein level and the number of GFP-LC3 dots while increased p62 protein level compared to MI/R model group, suggesting that vitexin may improve myocardial damage by inhibiting autophagy of cardiomyocytes in MI/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Aer H9c2 cells were treated with or without vitexin, the puncta formation of GFP-LC3 was determined under uorescent microscopy (Olympus BX5) as the previous study described. 15 Cells were considered to have accumulated autophagosomes when more than 5 puncta were counted.…”
Section: Fluorescence Microscopymentioning
confidence: 99%
“…Vitexin (apigenin-8-C-glucoside) is an active component found in abundance in most medicinal plant species such as pearl millet [55], hawthorn [56], bamboo [57], and Ficus deltoidea [58]. The compound is said to possess a number of pharmacological properties including anticancer [59], antinociceptive [60], antiviral [61], anti-inflammatory [62], and anti-AD [63]. However, this review will be focusing on the anti-AD and antineuroinflammatory properties that the vitexin compound possesses.…”
Section: Vitexinmentioning
confidence: 99%
“…This mechanism of MAPK8 signaling is mediated by BCL2 (B cell leukemia/lymphoma 2) phosphorylation (on Thr69, Ser70, and Ser87) that disrupts the interaction of BCL2 with BECN1 (beclin 1, autophagy related) and initiates BECN1-dependent autophagy [5]. Subsequent studies have provided strong support for this role of MAPK8 in autophagy [619], although contributing roles for MAPK9 [2023] and alternative potential functions of MAPK8 related to autophagy have also been reported [2429]. …”
Section: Introductionmentioning
confidence: 99%